Which Method for Diagnosing Small Fiber Neuropathy? - Fabry, Vincent; Gerdelat, Angélique; Acket, Blandine; Cintas, Pascal; Rousseau, Vanessa; Uro-Coste, Emmanuelle; Evrard, Solène M.; Pavy-Le Traon, Anne (Frontiers in Neurology, 2020)
Introduction - Small fibre neuropathies (SFN) induce pain and/or autonomic symptoms. The diagnosis of SFN poses a challenge because the role of skin biopsy as a reference method and of each neurophysiological test remain to be discussed. This study compares six methods evaluating small sensory and autonomic nerve fibres: skin biopsy, Quantitative Sensory Testing (QST), quantitative sweat measurement system (Q-Sweat), Laser Evoked Potentials (LEP), Electrochemical Skin Conductance (ESC) measurement and Autonomic CardioVascular Tests (ACVT). Methods - This is a single centre, retrospective study including patients tested for symptoms compatible with SFN between 2013 and 2016 using the afore-mentioned tests. Patients were ultimately classified according to the results and clinical features as "definite SFN", " possible SFN" or "no SFN". The sensitivity (Se) and specificity (Sp) of each test were calculated based on the final diagnosis and the best diagnostic strategy was then evaluated. Results – Two hundred and forty-five patients were enrolled (164 females (66,9%), age: 50.4 ± 15 years). The results are as follows: skin biopsy: Se = 58%, Sp = 91%; QST: Se = 72%, Sp = 39%; Q-Sweat: Se = 53%, Sp = 69%; LEP: Se = 66%, Sp = 89%; ESC: Se = 60%, Sp = 89%; Cardiovascular tests: Se = 15%, Sp = 99%. The combination of skin biopsy, LEP, QST and ESC has a Se of 90% and a Sp of 87%. Conclusion - Our study outlines the benefits of combining skin biopsy, ESC, LEP and QST in the diagnosis of SFN.